q-Apostol–Euler Polynomials and q-Alternating Sums - Luo, Q.-M. (Український математичний журнал, 2013)
Basic properties are established and generating functions are obtained for the q -Apostol–Euler polynomials. We define q -alternating sums and obtain q -extensions of some formulas from Integral Transform. Spectr. Funct., 20, 377–391 (2009). We also deduce an explicit relationship between the q -Apostol–Euler polynomials and the q -Hurwitz–Lerch zeta-function. Встановлено основні властивості та твірні функції q-полiномiв Апостола-Ейлера. Визначено q-знакозмінні суми та отримано q-продовження деяких формул з [Integral Transform. Spec. Funct.-2009.-20.-P. 377-391]. Виведено також явне співвідношення між q-поліномами Апостола-Ейлера i q-дзета-функцією Хурвіца-Лерча.